Theory and applications of fluid mechanics including hydraulic machines - Subramanya, K. (TMH outline series, 1995)
In SI units, the book presents the principles and applications of fluid mechanics through a series of solved examples, numerical problems and multiple-choice objective quesions. A chapter on hydraulic machines has been included.